That '70s Show : Season 1 Disc 2 - Trainer, David; Kutcher, Ashton; Danny Masterson; Debra Jo Rupp; Laura Prepon; Mila Kunis; Wilmer Valderrama; Topher Grace (USA 20th Century Fox, 1998)
Eric Forman is a typical high school student growing up in Wisconsin in 1976 with his family and his friends. Together, they have the same kind of joys and sorrows that just about every teenager has while growing up. This show parodied many of the attitudes, events and fads of the 70's, along with those who grew up at the time and are now in their 30's-40's.
This show explains what it was like for a group of 17 year olds living in 1976.
Language : English Subtitles : English
Keywords: Comedy -- Tv Series